Pemanfaatan Kulit Kakao sebagai Biosorben: A Review - Fajrul Alif Arifin; Edi Nasra (MASALIQ, 2026)
Water pollution caused by heavy metals and dyes from industrial waste has received considerable research attention. However, studies specifically synthesizing the use of cocoa pod husk waste (Theobroma cacao L.) as a biosorbent for both pollutant groups remain limited. This study aimed to examine the potential and characteristics of cocoa pod husks as a biosorbent and to identify the conditions affecting the adsorption of heavy metals and dyes. This study employed a qualitative approach with a literature review design encompassing several scholarly articles on adsorption using cocoa pod husks. The findings showed that optimum adsorption conditions were generally achieved at near-neutral solution pH, adsorbate concentrations below 100 ppm, and contact times of less than 100 minutes. Dye adsorption tended to follow the Langmuir isotherm model, whereas heavy metal adsorption was better described by the Freundlich isotherm model. These findings indicate that cocoa pod husks have the potential to serve as a biosorbent in the treatment of water contaminated with heavy metals and dyes. Their adsorption efficiency is primarily affected by solution pH, contact time, and initial adsorbate concentration. This study contributes to the development of natural material-based biosorption technology while supporting the valorization of agricultural waste as a valuable material for wastewater treatment.